Cross Sectional Study to Inquire Hepatitis B Immunization Status and in Immunized Individuals Knowledge about Post Vaccination Serological Titer Status among Nursing Staff and Lab Technicians in a Teaching Hospital of Ujjain - Rashmi Bhujade; Pawan Pathak; Tarique Ibrahim; Konika Jain (Medsci Publications, 2019)
Background: More than 2 billion people worldwide  are  infected with Hepatitis B Virus(HBV) infection, among them, around 360 million individuals are chronically infected and are at risk of serious illness and death, especially from fulminant  hepatic failure ,cirrhosis and hepato-cellular carcinoma (HCC).  HBV is commonest blood-borne hepatitis and significant healthcare occupational pathogen.HBV infection can be prevented by vaccine. Material and Method: Hepatitis B immunization status and  in immunized  individual  status of post vaccination Anti Hbs titer of the health care providers (nursing staff and lab technicians) in teaching hospital  was assessed by a cross sectional study using a semi structured proforma. Results: Only 23 % study participants were fully immunized against hepatitis B. No one was aware about importance of post vaccination anti HBs titer. No one had ever estimated or tested for their post vaccination anti HBs titer. Hepatitis B immunization status of study participants was found to be significantly (<0.05) associated with sex and year of experience of study participants. Conclusion: Immunization coverage of hepatitis B among staff nurses and lab technicians found to be low. Anti HBS titer was not utilized as a tool to assess immunity provided by hepatitis B vaccine.